In order to solve using elimination you have to “eliminate” one of the variables (get it?).

The x values, -8x and 8x, can be eliminated by just adding them together (-8x+8x=0), sometimes you would need to multiply one of the variables to make it equal to the other.

Now you have to add the y values together, (8y+ -5y= 3y) and lastly the 24 and 0 (24+0=24) which add to 24.

You’re now left with 3y=24, in order to get rid of the coefficient, the number in front of y, you need to divide both terms by 3, (3y÷3=y) (24÷3=8) and finally you get y=8.

You now need to plug in the y value into one of the original equations, for example 8x-5y=0 turns to -> 8x-5(8)=0. You multiple -5 by 8 to get -40

8x-40=0

Now to get the variable by itself you add 40 to both sides of the equation, removing -40 from the left side of the equal sign and bringing it to the right.

8x=40

Divide both terms by 8 to get x by itself

x=5

And there you go, x=5 and y=8.

To doubly so make sure you got it right you could plug in the variables to the equation you didn’t use

x= 5

y=8

the other person gave you the explanation

Answer:Step-by-step explanation:eliminate” one of the variables (get it?).